2013
DOI: 10.1111/dme.12131
|View full text |Cite
|
Sign up to set email alerts
|

Urinary sulphate excretion and progression of diabetic nephropathy in Type 1 diabetes

Abstract: High urinary sulphate excretion was significantly associated with slower decline in (51)Cr-EDTA-assessed GFR in diabetic nephropathy, independent of known progression promoters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…In a post-hoc analysis study it was found that urinary sulfate (sulfate in the urine is the metabolic end product of H 2 S) was negatively associated with albuminuria suggesting the authors to conclude higher urinary sulfate concentration is associated with reduced renal risks in type 2 diabetic nephropathy [183]. Similar results were reported from another independent post-hoc prospective, randomized, controlled trial in which it was noticed that high urinary sulfate excretion was associated with slower decline of assessed GFR in diabetic nephropathy patients, and this was independent of known end-stage renal disease progression promoters [184]. All these above reports clearly establish a link between diabetes, hypertension and kidney dysfunction where H 2 S plays a key role to modulate hypertension and kidney dysfunction in diabetes.…”
Section: Other Metabolic Disorders: H2s Is a Modulator Of Renal Dysupporting
confidence: 64%
“…In a post-hoc analysis study it was found that urinary sulfate (sulfate in the urine is the metabolic end product of H 2 S) was negatively associated with albuminuria suggesting the authors to conclude higher urinary sulfate concentration is associated with reduced renal risks in type 2 diabetic nephropathy [183]. Similar results were reported from another independent post-hoc prospective, randomized, controlled trial in which it was noticed that high urinary sulfate excretion was associated with slower decline of assessed GFR in diabetic nephropathy patients, and this was independent of known end-stage renal disease progression promoters [184]. All these above reports clearly establish a link between diabetes, hypertension and kidney dysfunction where H 2 S plays a key role to modulate hypertension and kidney dysfunction in diabetes.…”
Section: Other Metabolic Disorders: H2s Is a Modulator Of Renal Dysupporting
confidence: 64%
“…Here, adjustment for 24-h urinary urea excretion on top of potential confounders had no effect on the statistical significance of the association between urinary sulfate excretion and all-cause mortality. This is in line with previous studies of renal transplant recipients and patients with diabetes mellitus type 1 nephropathy in which the association of sulfate excretion with all-cause mortality or renal disease progression was shown to be independent of dietary protein intake (1,45).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies of high-risk populations have shown that urinary excretion of thiosulfate and sulfate are associated with a favorable CV risk profile and survival in renal transplant recipients(45) and preservation of renal function in patients with diabetes (1,46). Our…”
Section: -mentioning
confidence: 99%
“…However, in renal transplant recipients and patients with 320 diabetes mellitus type 1 nephropathy the association of sulfate excretion with all-cause 321 mortality or renal disease progression was shown to be independent of dietary protein 322 intake. [1,2] Perhaps sulfate production through oxidation of SAAs is a stronger determinant,especially because of the intermediate enzymatic production of H 2 S as part of this process that 324 could explain the benefit of high urinary sulfate excretion. Accordingly, various preclinical studies have convincingly shown H 2 S to be protective in 330 HF.…”
Section: Catabolism 307mentioning
confidence: 99%